Job Enrichment Model Development Human-Centered Design in Reducing Job Hopping Intention of Generation Z Employees in North Sumatra - Taufik Yuandika Bahri (STIE Amkop Makassar, 2026)
The phenomenon of job hopping intention among Generation Z employees has become a serious challenge for organizations, particularly in North Sumatra, which is experiencing economic growth. This study aims to develop a Human-Centered Design (HCD)–based job enrichment model to reduce job hopping intention among Generation Z employees. This study employs a mixed-methods approach with a sequential exploratory design. The qualitative phase was conducted through in-depth interviews and Focus Group Discussions (FGDs) to explore the work needs, preferences, and perceptions of Generation Z toward their jobs. The qualitative findings were used to formulate contextually relevant dimensions of HCD-based job enrichment. The quantitative phase involved a survey of 150 Generation Z employees across various service, manufacturing, and banking companies in North Sumatra. The sampling technique used was purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM-PLS) with SmartPLS. The results indicate that HCD-based job enrichment has a positive and significant effect on work engagement and job satisfaction, and a significant negative effect on job hopping intention. Work engagement and job satisfaction were found to partially mediate the relationship between job enrichment and job hopping intention. This study produces a conceptual and practical model for the development of HCD-based job enrichment that can be implemented by organizations to reduce job hopping intention among Generation Z employees in North Sumatra.